Influence of Postemergence Dicamba/Glyphosate Timing and Inclusion of Acetochlor as a Layered Residual on Weed Control and Soybean Yield - Striegel, Sarah; Oliveira, Maxwel C.; DeWerff, Ryan P.; Stoltenberg, David E.; Conley, Shawn P.; Werle, Rodrigo (Frontiers in Agronomy, 2021)
Roundup Ready 2 Xtend® [glyphosate- and dicamba-resistant (DR)] soybean is a novel trait option for postemergence (POST) control of herbicide-resistant broadleaf weeds in soybean. With increased use of labeled dicamba products POST in DR soybean and recommendations to include a soil-residual herbicide POST (e.g., layered residual approach), research on how combinations of these approaches influence weed control, weed seed production, and soybean grain yield is warranted. The objective of this research was to evaluate the effects of (1) flumioxazin applied preemergence (PRE) followed by (fb) dicamba plus glyphosate applied POST at different developmental stages and (2) acetochlor POST as a layered residual approach on weed control, weed seed production, and soybean yield to determine the optimal POST timing in DR soybean. A field study was conducted in Wisconsin at three sites in 2018 and four sites in 2019 to evaluate flumioxazin (43.4 g ai ha-1, WDG 51%) PRE fb dicamba (560 g ae ha-1, SL) plus glyphosate (1101 g ae ha-1, SL) POST in DR soybean at three stages: early-POST (EPOST, V1-V2), mid-POST (MPOST, V3-V4), and late-POST (LPOST, V5-V6/R1) with or without a soil-residual herbicide POST (acetochlor, 1262 g ai ha-1, ME). Weed community composition was site-specific; difficult-to-control broadleaf species included giant ragweed (Ambrosia trifida L.) and waterhemp [Amaranthus tuberculatus (Moq.) J.D. Sauer]. Dicamba plus glyphosate applied MPOST and LPOST provided greater control, weed biomass reduction, and density reduction of giant ragweed and waterhemp when compared with EPOST treatments. Giant ragweed and waterhemp had not reached 100% cumulative emergence at EPOST, and plants that emerged after EPOST produced seed. There was some benefit to including acetochlor as a layered residual at EPOST as indicated by a residual by POST timing interaction for waterhemp density reduction. Complete waterhemp control was not attained at one site-year. For remaining site-years, dicamba plus glyphosate applied MPOST (V3-V4) provided season-long weed control, reduced weed seed production, and optimized soybean grain yield compared with other POST treatments. Results highlight the importance of timely POST applications and suggest utilization of a POST layered residual needs to be timed appropriately for the window of active weed species emergence.